Coexistence of amyotrophic lateral sclerosis with neuro‐Behçet's disease presenting as a longitudinally extensive spinal cord lesion: clinicopathologic features of an autopsied patient. Issue 2 (30th September 2013) - Sato, Tomoe; Ouchi, Haruka; Shimbo, Junsuke; Sato, Aki; Yamazaki, Motoyoshi; Hashidate, Hideki; Igarashi, Shuichi; Kakita, Akiyoshi
<x xml:space="preserve">Abstract</x> We report the clinical and autopsy features of a 65‐year‐old Japanese man who clinically exhibited overlap of both neuro‐Behçet's disease (NBD) and amyotrophic lateral sclerosis (ALS). The patient had a HLA‐B51 serotype, a recent history of uveitis and had suffered paraparesis, sensory and autonomic disturbance, frontal signs and tremor. A brain and spine MRI study revealed a longitudinally extensive thoracic cord (Th) lesion, but no apparent intracranial abnormalities. The lesion extended ventrally from Th4 to Th9, exhibiting low intensity on T1‐weighted images, high intensity on T2‐weighted and fluid‐attenuated inversion recovery images and gadolinium enhancement. The patient's upper and lower motor neuron signs and sensory disturbance worsened and he died 16 months after admission. At autopsy, the spinal cord and brain exhibited characteristic histopathological features of both NBD and ALS, including chronic destruction of the ventral thoracic white and gray matter, perivascular lymphocytic infiltration, binucleated neurons, lower and upper motor neuron degeneration, Bunina bodies and skein‐like inclusions. Although incidental coexistence of these rare disorders could occur in an individual, this case raises the possibility of a pathomechanistic association between NBD and ALS.